2016
DOI: 10.1111/1755-5922.12215
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol therapy improves vascular endothelial function in subjects at risk for cardiovascular diseases: a meta‐analysis of randomized controlled trials

Abstract: Allopurinol therapy is associated with significantly improved endothelial function in subjects at risk of CVD risks, and the beneficial effects of allopurinol seemed to be more remarkable in patients with normal UA at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 51 publications
(142 reference statements)
1
27
2
Order By: Relevance
“…They concluded that febuxostat improved endothelial dysfunction, but they used asymmetric dimethylarginine as the index of endothelial dysfunction. Concerning allopurinol, a meta‐analysis of 10 randomized controlled trials demonstrated that subjects treated with allopurinol exhibited a significantly greater improvement in FMD compared with controls . In the current study, there was no significant difference in the change in FMD by treatment between the febuxostat and allopurinol group.…”
Section: Discussioncontrasting
confidence: 58%
“…They concluded that febuxostat improved endothelial dysfunction, but they used asymmetric dimethylarginine as the index of endothelial dysfunction. Concerning allopurinol, a meta‐analysis of 10 randomized controlled trials demonstrated that subjects treated with allopurinol exhibited a significantly greater improvement in FMD compared with controls . In the current study, there was no significant difference in the change in FMD by treatment between the febuxostat and allopurinol group.…”
Section: Discussioncontrasting
confidence: 58%
“…31,32,33 On the other hand, its effect on endothelial dysfunction features prominently in some other studies and a few meta-analyses have been published to summarize these effects in a small number of RCTs that included patients labeled as at risk of cardiovascular disease. [34][35][36] All showed a statistically significant benefit of allopurinol therapy with mean increases in brachial artery flowmediated vasodilatation by respectively 2.50% (95% CI 0.15-4.84), 34 2.75% (95% CI 2.49-3.01), 35 and 1.67% (95% CI 0.83-2.50). 36 Two of these analyses also reported the effects on forearm blood flow in response to acetylcholine via VOP, with increases of respectively 68.80 (95% CI 18.70-118.90) 34 and 2.62 (95% CI 2.32-2.91).…”
Section: Discussionmentioning
confidence: 97%
“…[34][35][36] All showed a statistically significant benefit of allopurinol therapy with mean increases in brachial artery flowmediated vasodilatation by respectively 2.50% (95% CI 0.15-4.84), 34 2.75% (95% CI 2.49-3.01), 35 and 1.67% (95% CI 0.83-2.50). 36 Two of these analyses also reported the effects on forearm blood flow in response to acetylcholine via VOP, with increases of respectively 68.80 (95% CI 18.70-118.90) 34 and 2.62 (95% CI 2.32-2.91). 35 These metaanalyses included patients with different comorbidities and reached the conclusion that allopurinol has the potential to enhance endothelial function in general without specifying a specific patient population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most internists stated that AHU treatment is effective and confirmed the need to reach a goal treatment for SUA levels <6 mg/dL. Allopurinol remains the firstline approach to AHU treatment, 28 although 50% of internists consider it useful treating AHU with febuxostat. Febuxostat can be used in patients with mild-tomoderate renal or hepatic involvement, which is frequently observed in internal medicine patients.…”
Section: Discussionmentioning
confidence: 99%